2015
DOI: 10.1093/cercor/bhv113
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Cognitive Mechanism of Mental Representational Change During Chunk Decomposition: A Parametric fMRI Study

Abstract: Chunk decomposition plays an important role in cognitive flexibility in particular with regards to representational change, which is critical for insight problem solving and creative thinking. In this study, we investigated the cognitive mechanism of decomposing Chinese character chunks through a parametric fMRI design. Our results from this parametric manipulation revealed widely distributed activations in frontal, parietal, and occipital cortex and negative activations in parietal and visual areas in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 57 publications
5
76
0
4
Order By: Relevance
“…The behavioral data showed that participants were faster on tasks requiring a Type 1 strategy for automatic chunk decomposition than when Type 2 deliberate chunk decomposition was required. This replicated previous findings that show differences in response times for different chunk decomposition strategies (Tang et al, 2016;Wu et al, 2013;Zhang et al, 2015). These results also replicated previous studies showing that the characters hypothesized as requiring automatic processes were solved more quickly than those hypothesized requiring deliberate processes.…”
Section: Insert Figure 3 and Table 2 About Here Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The behavioral data showed that participants were faster on tasks requiring a Type 1 strategy for automatic chunk decomposition than when Type 2 deliberate chunk decomposition was required. This replicated previous findings that show differences in response times for different chunk decomposition strategies (Tang et al, 2016;Wu et al, 2013;Zhang et al, 2015). These results also replicated previous studies showing that the characters hypothesized as requiring automatic processes were solved more quickly than those hypothesized requiring deliberate processes.…”
Section: Insert Figure 3 and Table 2 About Here Discussionsupporting
confidence: 90%
“…Chunk decomposition tasks that are reliant on either automatic or deliberative processing avoids the complexity of distinguishing the products of two processes that occur in the conflict problems typically used in tests of dual process theory. Chunk decomposition tasks require participants to decompose their mental representations into their component elements to form an alternative representation (Tang et al, 2016). Chunk decomposition tasks are simple but ingenious, as they guide participants into using either automatic or deliberate processing.…”
Section: Chunking Decomposition Tasks In Dual Process Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, we proposed a “representational change account” for cognitive reappraisal specific to a given unpleasant situation (such as viewing a negative IAPS picture). Ohlsson and Knoblich established representational change theory for creative insight problem solving, which suggests that problem solvers initially have a low probability of success because they retrieve inappropriate knowledge and set unnecessary constraints on the problem and that only when they break these inappropriate mental sets and establish a new but suitable representation of the problem can they have success in a seemingly unsolvable insight problem ( Ohlsson, 1984 , 1992 ; Knoblich et al, 1999 , 2001 ; Luo et al, 2006 ; Wu et al, 2009 , 2013 ; Huang et al, 2015 ; Tang et al, 2016 ). It is reasonable for us to propose that similar processes can also occur in cognitive reappraisal’s regulation of emotion: when encountering an apparently unpleasant stimulus, such as a picture of vomitus, people’s initial feeling or intuitive emotional response can be disgust; only when they have restructured the situation and given the scene a new meaning (for instance, reinterpreting the vomitus as a sign of pregnancy for a woman who wants to have a baby) can these negative feelings be altered.…”
Section: Discussionmentioning
confidence: 99%